Pharmacokinetic and pharmacodynamic effects of midodrine on blood pressure, the autonomic nervous system, and plasma natriuretic peptides: a prospective, randomized, single-blind, two-period, crossover, placebo-controlled study - Lamarre-Cliche, Maxime; Souich, Patrick du; Champlain, Jacques de; Larochelle, Pierre (Clinical therapeutics, 2008)
Background: Midodrine is an α-agonist prodrug of desglymidodrine (DGM) that has been reported to be of clinical benefit in patients with neurocardiogenic syncope. Its effects may be mediated not only by its hypertensive properties but also by its neurohumoral influences independent of blood pressure (BP). Objective: The present study aimed to simultaneously characterize the effects of midodrine on BP, plasma catecholamines, plasma atrial natriuretic peptide (ANP), and power spectral analysis of heart rate (HR) in healthy volunteers. Methods: This was a prospective, randomized, single-blind, 2-period, crossover study in which a single, oral, 5-mg dose of midodrine was compared with placebo. The washout period between midodrine and placebo was 1 week. The study parameters included plasma DGM (as measured by high-performance liquid chromatography [HPLC]); systolic and diastolic BP (as measured with an oscillometric monitor); HR; plasma catecholamines (measured by HPLC); plasma ANP, also known as venous return (measured by a radio-immunoassay); and low- and high-frequency HR variation (calculated from computerized 5-minute electrocardiographic recordings). All study parameters were measured simultaneously 12 times just before and over a period of 8 hours after drug administration. Results: Fifteen healthy nonsmoking male subjects (14 white, 1 black; mean [SD] age, 28.6 [4.7] years; weight, 74.5 [16.4] kg; seated BP, 109.9 [9.0]/73.6 [9.5] mm Hg; seated HR, 63.8 [8.4] bpm) were randomized. No significant effects of midodrine on BP were observed. At C max, midodrine decreased norepinephrine from 188.4 (30.6) to 162.5 (29.8) pg/mL ( P = 0.011) and HR from 57.2 (7.3) to 54.9 (6.6) bpm ( P = 0.022). A significant correlation was found between DGM concentration and HR ( ϕ -0.61; P = 0.014). A DGM-related increase in plasma ANP (+29.6 [90.0] fmoL/mL) was observed. Conclusion: This study in healthy male volunteers found that midodrine has sympatholytic influences that are independent of BP but related to augmented venous return.